Wat het van die land geword? Die psalms (veral Psalms 1 en 2) oor die land, gelees teen die agtergrond van Josua 1 - Helberg, J. L. (Old Testament Essays, 2005)
What happened to the land? The psalms (especially Psalms 1 and 2) on the issue of the land, read against the background of Joshua 1. The promised land is absent from the introductory psalms and the theme does not receive the intensive attention and focus which one would expect on account of its important place in God's covenant promises to Israel. In search of a reason for this, the psalms, especially Psalms 1 and 2, are viewed against the background of Joshua 1:5-9. Joshua's commission to conquer the land exhibits close connections with the initial verses of Psalm 1. Attention is given to the place of the land in the psalms as well as that of Jerusalem, Zion and the sanctuary. Attention is furthermore given to man's relationship with the earth. The finding is that in the psalms the land is placed and relativized in the framework of God's kingdom. In the promise to Abraham this kingdom was regarded as a universal kingdom. Fellowship with God in accordance with his Torah (Law/Word) is the determining factor in the psalms. In God's kingdom justice is demanded from and toward all. Time and expectation on the path of life is even more important than place.
free